Phytochemical characterization and anti-arthritic potential of green-synthesized CuO nanoparticles derived from the Bistorta amplexicaulis root extract - Babar, Mahrukh; Aslam, Bilal; Faisal, Muhammad Naeem; Malik, Abdul; Akhtar, Suhail; Fatima, Sabiha; Majeed, Wafa; Umer, Asher; Farooq, Muhammad Akmal (Frontiers in Pharmacology, 2024)
Rheumatoid arthritis is an autoimmune disease that mainly causes joint damage. Patient experiences loss of appetite, pain, fever and fatigue. The present study was designed to phytochemically characterize and evaluate the anti-arthritic activity of green synthesized Copper oxide (CuO) nanoparticles (NPs) using hydroalcoholic extract of Bistorta amplexicaulis roots in adjuvant-induced arthritic rat model. For this purpose, crude powdered plant was used for proximate analysis and plant extract was assessed for qualitative phytochemical analysis, mineral contents, flavonoid and phenolic contents as well quantitative phytochemical analysis through Reversed Phase High Performance Liquid Chromatography (RP-HPLC) and Fourier Transform Infrared Spectroscopy (FT-IR). In-vitro antioxidant activity of both extracts was determined by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay. Biosynthesized CuO NPs from Bistorta amplexicaulis extract showed anti-arthritic activity due to the presence of flavonoids and phenols which showed pain reliever effect by blocking the cyclo-oxygenase enzyme and has immune suppressant activity thus securing the joint from destruction. The nanoparticles were characterized by zeta size, zeta potential, Scanning Electron Microscopy (SEM) and FT-IR. Forty-eight albino rats were divided randomly into 6 treatment groups. Result of zeta size and zeta potential of nanoparticles was 186.8 nm and -9.23 mV respectively. Joint stiffness, spleen weight, thymus weight and paw thickness showed significant decrease after treatment with NPs. The hematological parameters such as Red Blood Cells (RBCs) and hemoglobin showed significant increase while platelets and White Blood Cells (WBCs) showed significant decrease in NPs treated groups. C-Reactive Protein (CRP), Rheumatoid factor (Rf) level, liver and kidney function biomarkers, Tumor Necrosis Factor-α (TNF-α) and Interleukin-6 (IL-6) levels showed a significant decrease with both low and high doses of green synthesized CuO nanoparticles from Bistorta amplexicaulis root extract. Final data was analyzed by one way and two-way analysis of variance (ANOVA) and Tuckey's multi-comparison test. So, from this study it was concluded that both plant roots extract and green synthesized CuO nanoparticles have anti-arthritic potential but CuO NPs showed remarkable results.